Many faces of FoMO: A qualitative in-depth investigation of context-specific experiences, emotions, and coping strategies - Diana Jaworska (PLoS ONE, 2025)
This study examines how individuals experience fear of missing out (FoMO) across online and offline contexts and the strategies they use to cope. Sixteen individual in-depth interviews (IDIs) with participants aged 18–35 revealed three categories of FoMO: (1) FoMO related to social media, (2) offline FoMO intensified by social media, and (3) solely offline FoMO. Each category features distinct emotional and behavioral responses, with universal coping strategies like distraction, self-reflection, and support-seeking, alongside social media-specific methods such as limiting information access and engaging in a social media detox. This study uniquely encompasses multiple FoMO contexts within a single framework, providing a more comprehensive view of FoMO’s emotional and behavioral impacts. Findings broaden the understanding of FoMO beyond social media, offering valuable insights for mental health professionals and social media platforms in addressing its diverse effects on well-being.